Resetting Bounding Nodes in Acquiring Spanish - Cebreiros, Ramiro (Kansas Working Papers in Linguistics, 1996)
This paper addresses the issue of whether L2 learners can reset parameters, by testing English speakers learning Spanish on their ability to reset the bounding node parameter. The bounding nodes are : IP and NP in English, CP and NP in Spanish. Subjects were given a grammaticality judgment task in Spanish that included wh-island and complex NP structures. Results show that they rejected most of the wh-structures (62.5%). This suggests that they are still transferring the bounding nodes from English. However, they rejected the complex NP structures at a higher rate (96%) suggesting that they are beginning to reset the bounding node parameter.